Deposition Growth and Morphologies of C60 on DTDCTB Surfaces: An Atomistic Insight into the Integrated Impact of Surface Stability, Landscape, and Molecular Orientation. Issue 17 (1st September 2015) - Han, Guangchao; Shen, Xingxing; Yi, Yuanping
Abstract : The influence of stability, landscape, and molecular orientation of different donor surfaces on fullerene packing and donor–fullerene interface morphologies are analyzed comprehensively through state‐of‐the‐art atomistic simulations taking the DTDCTB‐C60 system as an example. The results provide helpful insight into the formation of crystalline fullerene in the active layer to achieve efficient charge separation for organic solar cells.